Les licences professionnelles, une construction locale et éclectique - Catherine Agulhon (Cahiers de la Recherche sur l'Education et les Savoirs)
The creation of professional “licence” or bachelor programs were quickly implemented as well as monitored in great detail. These programs seem to represent a change in the contents of knowledge delivered by universities. This shift represents the professionalization of training considered to be more pragmatic, empirical and based on the work sphere. The systematic analysis of the names and contents of such training programs explains how the logic of competence and «savoir-faire» were integrated into universities. These concepts have participated in the transformation of the missions undertaken by universities.